Study on the Effectiveness of Cardiopulmonary Resuscitation in Elderly Patients Presenting with Cardiopulmonary Arrest on Arrival - Hagiwara, Shuichi; Kaneko, Minoru; Murata, Masato; Aoki, Makoto; Nakajima, Jun; Kanbe, Masahiko; Ohyama, Yoshio; Tamura, Jun'ichi; Oshima, Kiyohiro (Internal Medicine, 2015)
Objective This study was conducted to determine whether a policy of not attempting to resuscitate patients who are 80 years of age and older with cardiopulmonary arrest on arrival is justifiable. Methods The protocol of this study was approved without the need for informed consent by the research ethics board of Gunma University Hospital. We prospectively analyzed patients with cardiopulmonary arrest on arrival that was due to an intrinsic reason who were taken to Gunma University Hospital between January 2013 and March 2014. The patients were divided into two groups: patients who were less than 80 years of age (L group) and those aged 80 years and older (H group). We compared the patients' characteristics, including the etiology of cardiac arrest, and the prognosis between the two groups. Results A total of 103 patients with cardiopulmonary arrest on arrival were enrolled. There were no significant differences in the patients' characteristics, such as age, sex, witness and bystander cardiopulmonary resuscitation, and transportation time between the two groups. The return of spontaneous circulation was obtained in 14 patients (25.5%) in the L group and in 9 patients (18.8%) in the H group; however, no significant difference was seen between the two groups. Two patients in the L group were in good neurological condition when they were discharged; however, the other patients did not survive. Conclusion Even patients 80 years of age and older can be resuscitated to spontaneous circulation. We do not endorse a policy that recommends not performing cardiopulmonary resuscitation based solely on the age of the patient.